Olive tree at the intersection of environment, public health, and One Health: a sustainable path to global wellbeing - Katsafadou, Angeliki I.; Prodromou, Sofia I.; Aalizadeh, Reza; White, Jason C.; Thomaidis, Nikolaos S.; Vizirianakis, Ioannis S.; Anastas, Paul T.; Kyriakides, Tassos C.; Pastides, Harris; Piscitelli, Prisco; Colao, Annamaria; Thompson, David C.; et al. (Frontiers in Public Health, 2025)
The olive tree and its derivatives—olives, olive oil, and their by-products—are foundational to the Mediterranean diet and are increasingly recognized for their roles in nutrition, medicine, and ecological sustainability. Indeed, one of the most prominent examples of sustainable production and consumption paradigm in a changing climate lies in the olive sector, approached within One Health framework, i.e., the interconnectedness of human health with animal and environmental health. This review explores the multifaceted roles of olive cultivation, olive oil production and consumption, and olive by-products in relation to health benefits, sustainable agriculture, and environmental impact. Olive oil consumption offers significant human health benefits, primarily involving its anti-inflammatory and antioxidant properties. These effects, largely attributed to its rich composition of monounsaturated fatty acids and other antioxidants, mediate its cardioprotective and neuroprotective roles. Beyond human health, olive oil cultivation and its by-products (such as pomace and mill wastewater) have gained attention as valuable feed additives in animal nutrition. These enhance livestock health and welfare, improve meat and dairy quality, and promote sustainable agricultural practices and bioenergy production—ultimately reducing environmental impact and supporting circular economies. From an environmental perspective, the olive sector contributes meaningfully to soil conservation, biodiversity support, and climate change mitigation through carbon sequestration and reduced greenhouse gas emissions. As such, the olive tree is more than a source of a valuable food product: it is a nexus of sustainable development, public health, and ecosystem stewardship. Considering the olive sector within the One Health paradigm highlights its relevance in addressing global challenges at the intersection of food systems, health, and environmental sustainability.